Pengaruh Keadilan Kompensasi, Motivasi Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Waroeng Spesial Sambal Yogyakarta - Ifriansyah, Rudy (208-7721)
Compensation, motivation and job satisfaction is directly related to the employees performance. Compensation, motivation and job satisfaction felt by employees can degrade performance or improve employee performance. Compensation in accordance with the expectations of employees and the employees were satisfied with their jobs will be motivated to improve performance so that will have an impact on increasing the companys overall performance. This research was conducted at Waroeng Spesial Sambal (SS) Yogyakarta. This study aims to determine the effect of compensation, motivation and job satisfaction on employee performance. The number of samples is set as many as 154 respondents using random sampling method. Results of the analysis showed that the variables of job satisfaction and work motivation positive effect on employee performance, while variable compensation is not successful in influencing the performance of employees.